2022
DOI: 10.1371/journal.ppat.1010485
|View full text |Cite
|
Sign up to set email alerts
|

The host inflammatory response contributes to disease severity in Crimean-Congo hemorrhagic fever virus infected mice

Abstract: Crimean-Congo hemorrhagic fever virus (CCHFV) is an important human pathogen. In cell culture, CCHFV is sensed by the cytoplasmic RNA sensor retinoic acid-inducible gene I (RIG-I) molecule and its adaptor molecule mitochondrial antiviral signaling (MAVS) protein. MAVS initiates both type I interferon (IFN-I) and proinflammatory responses. Here, we studied the role MAVS plays in CCHFV infection in mice in both the presence and absence of IFN-I activity. MAVS-deficient mice were not susceptible to CCHFV infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 66 publications
3
14
0
Order By: Relevance
“…For representative examples, in one study the entire viral propagation method was described as “CCHFV (strain IbAr10200) was propagated in Vero E6 cells”, with no specific details or reference to the literature [ 42 ]. A similar case was found, where the viral stock was amplified in HuH-7 cells [ 17 ]. In another study, the methods of viral propagation in SW-13 cells and plaque assay titration methods were referred to a Master’s thesis, which was not found by our search on the internet [ 43 ].…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…For representative examples, in one study the entire viral propagation method was described as “CCHFV (strain IbAr10200) was propagated in Vero E6 cells”, with no specific details or reference to the literature [ 42 ]. A similar case was found, where the viral stock was amplified in HuH-7 cells [ 17 ]. In another study, the methods of viral propagation in SW-13 cells and plaque assay titration methods were referred to a Master’s thesis, which was not found by our search on the internet [ 43 ].…”
Section: Introductionsupporting
confidence: 65%
“…We performed a comprehensive search for research papers describing CCHFV cell culture, which covered all-time literature in the PubMed and identified four cell lines of considerable popularity, Vero (E6) [ 4 , 13 , 14 , 16 27 ], SW-13 [ 8 , 17 21 , 24 , 26 , 28 – 41 ], HuH-7 [ 17 , 20 , 21 , 31 , 33 , 39 , 56 , 57 ] and BSR-T7/5 [ 4 , 57 59 ] (Fig. 1 and Additional file 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, future studies are recommended to investigate the potential use of kinase-targeting therapies (Bhullar et al, 2018) and dephosphorylation inhibitors such as TNF-b-specific inhibitor (Nie et al, 2013) as promising therapy strategies against CCHF. The latter approach was also proposed in a recent study by Golden et al, which demonstrated the protective effects of anti-TNF-b neutralizing antibodies in mice exposed to CCHF (Golden et al, 2022).…”
Section: Discussionmentioning
confidence: 97%
“…Mainly four TLRs (TLR-3,4,7, and 8) broadly act as viral antigenic receptors and play a crucial role against viral infections [ 102 ] whereas TLR-1,2,5,6,9–12 primarily work against bacterial infection [ 102 ]. TLR3, which senses viral dsRNA and structured RNA, is associated with acute CCHF, and enhances the activity of the protein, can stimulate innate immune responses [ 103 106 ]. Therefore, the activity of these receptors with the desired vaccine candidate has been observed in this study.…”
Section: Discussionmentioning
confidence: 99%